2018
DOI: 10.1002/jcc.25227
|View full text |Cite
|
Sign up to set email alerts
|

On the ion‐pair dissociation mechanisms in the small NaCl·(H2O)6 cluster: A perspective from reaction path search calculations

Abstract: We performed reaction path search calculations for the NaCl·(H O) cluster using the global reaction route mapping (GRRM) code to understand the atomic-level mechanisms of the NaCl → Na + Cl ionic dissociation induced by water solvents. Low-lying minima, transition states connecting two local minima and corresponding intrinsic reaction coordinates on the potential energy surface are explored. We found that the NaCl distances at the transitions states for the dissociation pathways were distributed in a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Snapshots from the MD simulation illustrate the different states in Figure A. In fact, the TS in this one-dimensional projection corresponds to an ensemble of disparate states that do not single out well the actual TS in an enlarged multidimensional description. , This however is not a problem for our kinetic description using the GLE, since non-Markovian effects, caused by dimensional reduction, are fully accounted for. Note that the confinement potential U con ( x ) changes the barrier height from the CP to the TS state slightly, as seen by comparing U ( x ) (solid line) and U ( x ) – U con ( x ) (broken line) in Figure A.…”
Section: Simulation Model and Theoretical Frameworkmentioning
confidence: 99%
“…Snapshots from the MD simulation illustrate the different states in Figure A. In fact, the TS in this one-dimensional projection corresponds to an ensemble of disparate states that do not single out well the actual TS in an enlarged multidimensional description. , This however is not a problem for our kinetic description using the GLE, since non-Markovian effects, caused by dimensional reduction, are fully accounted for. Note that the confinement potential U con ( x ) changes the barrier height from the CP to the TS state slightly, as seen by comparing U ( x ) (solid line) and U ( x ) – U con ( x ) (broken line) in Figure A.…”
Section: Simulation Model and Theoretical Frameworkmentioning
confidence: 99%
“…Understanding the microscopic behavior of salts in solution is one of the most fundamental questions in physical chemistry. The salt–water complex NaCl­(H 2 O) is a basic model system for understanding the solvation of salts in water at a molecular level. Recently, many theoretic and experimental studies have been performed on NaCl­(H 2 O) n clusters, such as ab initio calculations, argon-matrix infrared spectroscopy, helium-nanodroplet infrared spectroscopy, Fourier transform microwave spectroscopy, , and anion photoelectron spectroscopy . These studies have shown that small clusters NaCl­(H 2 O) n usually have several isomers close in energy due to the weak noncovalent interactions.…”
mentioning
confidence: 99%
“…A series of ion pairing systems are selected from the monoatomic to polyatomic ions. As the most widely studied electrolyte through experimental techniques and theoretical simulations, 39,42,46–49 Na + –Cl − is chosen as the representative electrolyte not only to provide benchmark to validate the proposed computational strategy here, but also to offer direct comparison to the association of polyatomic ions, Ca 2+ –CO 3 2− and Ca 2+ –HPO 4 2− . The selected two polyatomic ions, broadly existing in nature, play a pivotal role in biological environment and life activities, and have been studied with extensive experimental and computational data available for comparison 50–53 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of ion pairing systems are selected from the monoatomic to polyatomic ions. As the most widely studied electrolyte through experimental techniques and theoretical simulations, 39,42,[46][47][48][49] Na + -Cl À is chosen as the representative electrolyte not only to provide benchmark to validate the proposed computational strategy here, but also to offer direct comparison to the association of polyatomic ions, Ca 2+ -CO 3 2À and Ca 2+ -HPO 4…”
Section: Introductionmentioning
confidence: 99%